Pelatihan Usaha Roti dalam Rangka Menambah Penghasilan bagi Ibu Rumah Tangga di Kecamatan Tegineneng Kabupaten Pesawaran - Hendri , Hendri; Syarif, Arman (Jurnal Pemberdayaan Ekonomi, 2025)
Purpose: This program aims to enhance the entrepreneurial skills of housewives in Tegineneng District, Pesawaran Regency, through bread-making training as an alternative source of additional income, while fostering entrepreneurship based on local potential. Methodology/approach: The program was carried out using a participatory training approach, consisting of lectures, counseling, demonstrations of bread-making, packaging, and marketing strategies. Participants were provided with recipe modules and hands-on practice assistance. Evaluation data were collected through skill observations, interviews, and group discussions. Results/findings: The training successfully improved participants’ knowledge of proper bread production techniques, from raw material selection, fermentation processes, to packaging. In addition, participants’ skills in marketing products also increased. They demonstrated a mindset shift toward being more open to business opportunities, with some starting to produce and sell bread independently. Conclutions: The bread-making training program effectively equipped housewives with practical skills and entrepreneurial motivation. The combination of improved knowledge, production skills, and marketing abilities has created new business opportunities at the household level. Limitations: This activity was limited to participants within a single district and did not yet fully utilize digital technology for marketing. Moreover, long-term evaluation of post-training business performance has not been conducted. Contribution: The program makes a tangible contribution to local economic empowerment by utilizing the potential of housewives as human resources. This training model can be replicated in other regions to increase household income while strengthening the food-based MSME sector.